1993
DOI: 10.1016/0016-7037(93)90110-i
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diffusivity of boron in melts of haplogranitic composition

Abstract: A~~~-~erni~Asiatic of B in synthetic melts of hapl~~tic composition have been measured by the diffusion couple technique at 1 atm between 1200-1600°C. The compositional profiles were measured by ion microprobe and modelled using the Boltzmann-Matano formalism to retrieve compositionally dependent interdiffision coefficients.At the experimental conditions, &OS is found to exchange primarily with SiO, and the interdiffusion coefficient increases with increasing replacement of Si by B in the melt. No isotopic fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Until now it is still uncertain in which form the boron exists in the melt and how big is the boron isotope fractionation between the melt and tourmaline. Boron in the melt is thought to be in the form of tetrahedral B(OH) 4 -complexes (Pichavant, 1983;Chakraborty et al, 1993). However, Geisinger et al (1988) suggested that a substantial proportion of boron is in trigonal complexes in Al-rich granitic melts.…”
Section: Boron Isotope Geochemistry Of the Lavicky Tourmalinesmentioning
confidence: 99%
“…Until now it is still uncertain in which form the boron exists in the melt and how big is the boron isotope fractionation between the melt and tourmaline. Boron in the melt is thought to be in the form of tetrahedral B(OH) 4 -complexes (Pichavant, 1983;Chakraborty et al, 1993). However, Geisinger et al (1988) suggested that a substantial proportion of boron is in trigonal complexes in Al-rich granitic melts.…”
Section: Boron Isotope Geochemistry Of the Lavicky Tourmalinesmentioning
confidence: 99%
“…The diffusion of B in melilite, on the other hand, has not been studied. But generally speaking B diffusion in silicates is expected to be slow because B replaces Si (Chakraborty et al, 1993). Boron diffusion rates in albite and anorthte were reported as 2 x 10-17 = 3 x 10-16 cmVs at about 900-1050 "C (Giletti, 1997).…”
Section: Comparison Of Beryllium-boron System With Aluminum-magnesiummentioning
confidence: 99%
“…We thus suggest that kinetic fractionation during dehydration of both AOC or sediments could strongly control the Li isotopic composition of Grenada MIs, whereas the boron model is based on isotopic equilibrium dehydration. This difference relies on the slower diffusivity of B compared to Li [ Chakraborty et al , 1993].…”
Section: Discussionmentioning
confidence: 99%